2010
DOI: 10.1080/14631377.2010.518479
|View full text |Cite
|
Sign up to set email alerts
|

The macroeconomic implications of emigrants’ remittances in Romania, Bulgaria and Albania

Abstract: The process of transition in the Balkan economies was accompanied by large-scale emigration. The employment of a considerable part of their labour force abroad was accompanied by a massive inflow of remittances. Remittances are considered the basic gain of migration for the emigration countries and their main compensation for losing (temporarily or more permanently) a part of their labour force. Whether remittances contribute to the economic development of the country receiving them depends on how they are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…Clément () estimated that remittance flows boost consumption expenditures by 1.7 per cent in Tajikistan. Blouchoutzi and Nikas () observed that international remittances are a determining factor for household consumption expenditures in Romania, Bulgaria and Albania.…”
Section: Driving Factors To Remit and Uses Of Remittancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clément () estimated that remittance flows boost consumption expenditures by 1.7 per cent in Tajikistan. Blouchoutzi and Nikas () observed that international remittances are a determining factor for household consumption expenditures in Romania, Bulgaria and Albania.…”
Section: Driving Factors To Remit and Uses Of Remittancesmentioning
confidence: 99%
“…Macro and micro level empirical studies (country case studies using household surveys), supporting the optimistic view, reveal that remittances reduce income inequality, (Mughal, ), poverty (Jimenez‐Soto and Brown, ), infant mortality (Zhunio et al., ), child labour (Ebeke, ), malnutrition (Lu, ), and output volatility (Chama et al., ). Additionally, they promote economic growth (Cooray, ), financial sector development (Aggarwal, et al., ), and capital accumulation (Senbeta, ); increase the propensity to save (Ziesemer, ), aggregate labour supply (Posso, ), domestic investment (Blouchoutzi and Nikas, ), tax revenues (Abdih et al., ), and life expectancy (Zhunio et al., ); improve primary and secondary school attendance (Zhunio et al., ); and maintain macroeconomic stability (Spatafora, ).…”
Section: Introductionmentioning
confidence: 99%
“…Remittances are considered as compensation for emigration, which causes a decrease in the human capital in countries of origin of migrants, but also they can decrease labor supply and increase the income inequality. Blouchoutzi and Nikas (2010) analyzed the effects of remittances in the economies of Albania, Bulgaria, and Romania. The usage of remittances was mainly in the construction, purchase of the capital goods, transport, and financial services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Значај новчаних дознака из иностранства може се уочити на примеру три бал-канске земље, где је за период 1992-2008. година примећено да се укупни годи-шњи износ новчаних дознака повећава у складу са процентом БДП -5,5% у Руму-нији, 8,6% у Бугарској и 27% у Албанији, где се проценат подудара и са повећањем стопе индустријске производње [8].…”
Section: кључне речи: миграције имигранти нерегуларна имиграција пunclassified
“…Пре-ма извештају Међународне организације рада, 8 који је усвојен у јуну 2012. године, током претходне деценије укупно је око 20 милиона људи емигрирало, од којих су једна четвртина деца [12]. Подаци из Европске комисије говоре да је само у перио-ду 2010-2012. године у Европи забележено 30.146 жртава трговине људима, иако је стварни број сигурно много већи [13].…”
Section: кључне речи: миграције имигранти нерегуларна имиграција пunclassified